Perilaku Hidup Sehat dan Kejenuhan Akademik Mahasiswa Selama Pembelajaran Daring - Rian Ishak Nubatonis; Arthur Huwae (Kuras Institute, 2022)
The issue of COVID-19 pandemic has had a very significant impact and impact on the world of education. All academic activities are carried out online, causing students to experience academic burnout. The problem of academic saturation is expected to be handled appropriately by students so as not to risk short-term and long-term achievement. One of the predictable steps that can be taken is implementing healthy lifestyle behaviors. Therefore, this study aims to determine the relationship between healthy lifestyle behavior and student academic burnout during online learning. The method used is quantitative with a correlational design. The participants involved were 154 students using an incidental sampling technique. Measurement of the study using Health Promoting Lifestyle Profile II (α = 0.906) and School Burnout Inventory (α = 0.760), with data analysis using product moment correlation from Karl Pearson. The results of the study found that there was a negative relationship between healthy lifestyle behavior and student academic burnout during online learning (r = -0.149 with sig.= 0.033). These results indicate that the higher the healthy lifestyle behavior applied by students, the problem of academic burnout will be minimized properly.